Stanislavsky and pedagogy - Aquilina, Stefan (London ; New York : Routledge Taylor & Francis Group, 2024)
"Stanislavsky and Pedagogy explores current thinking around the pedagogical implications of Stanislavsky's work. The volume depicts the voices of a number of practitioners, teachers, and scholars who are themselves journeying with Stanislavsky, and who in his work find a potent instigator for their own pedagogical practice and study. This book outlines instances in which updated interpretations of Stanislavsky's pedagogy are adapted to cater for contemporary needs and scenarios. These include the theatre industry, new digital technologies, the need to develop playfulness, application to a broad repertoire, performance as pedagogy, university managerialism, and interdisciplinary crossovers with dance and opera. The pedagogies that emerge from these case-studies are marked by fluidity and non-fixity, and help to underscore the malleability of Stanislavsky's system. Stanislavsky and... is a series of multi-perspectival collections that bring the enduring legacy of Stanislavskian actor training into the spotlight of contemporary performance culture, making them ideal for students, teachers, and scholars of acting, actor training, and directing"--
Introduction / Stefan Aquilina -- Teaching Stanislavsky's core approach of action, imagination, and experiencing - and why it is still relevant for acting students and professionals / John Gillett -- Stanislavsky and the pedagogy of play / Hilary Halba -- When actors become birds: re-envisioning pedagogical frameworks in the rehearsal space / Julia Listengarten and Christopher Niess -- Framing Stanislavsky: online pedagogies in the Zoom era / Bella Merlin -- A slice of Zoom life: transforming actor training in a global pandemic / David Shirley -- Stanislavsky dances Argentine Tango: actionable knowledge on co-actor connection / Elien Hanselaer -- Towards a pedagogical vision for opera: the musico-dramatic text and Stanislavsky's 1922 staging of Eugene Onegin / Mario Frendo.
Includes bibliographical references and index.
Keywords: Stanislavsky, Konstantin, -- 1863-1938.; Acting -- Study and teaching; Essays